Konsep Maslahah dalam Metodologi Tarjih Muhammadiyah - Zakaria, Soni; Supriadi, Agus (Prodi HKI IAI Miftahul Ulum Pamekasan, 2024)
This article aims to analyze how the concept of maslahah is applied in the tarjih methodology in the Muhammadiyah tarjih council. There are three reasons why this research is important. First, Maslahah is a concept pioneered by ushul scholars, and its existence in the methodology of Islamic law istinbath many accept but also not a few who reject it as an epistemology of Islamic law. Second, Muhammadiyah as an Islamic-based community organization is one of the organizations engaged in da'wah, and has a Tarjih assembly as a forum tasked with studying and producing Islamic law in the form of tarjih decisions and fatwas. Third, through the Tarjih Assembly, which plays a role in issuing Tarjih decisions or fatwas on Islamic law, it does not escape using various Islamic legal methodologies used in the assembly. The results of this study show that the Muhammadiyah tarjih council uses maslahah considerations in legalizing certain problems. While the methods used in achieving maslahah include Qiyas, Istihsan, Maslahah Mursalah and saddu al-dzariat.